Factor structure of the Sleep Disturbance Scale for Children (SDSC) in those with Attention Deficit and Hyperactivity Disorder (ADHD) - Mancini, Vincent O. (Sleep Med X, 2019)
OBJECTIVE: To examine the factor structure of the Sleep Disorder Scale for Children (SDSC) in children and adolescents with attention deficit and hyperactivity disorder (ADHD). METHOD: The caregivers of 307 children with ADHD completed the SDSC. Standard and bifactor confirmatory factor analysis (CFA) evaluated the goodness-of-fit of competing factor structures. RESULTS: The original and unidimensional factor structure produced sub-optimal fit. Bifactor exploratory factor analysis (EFA) was performed to examine the underlying structure of the SDSC. A revised bifactor solution comprising six-specific factors and a general factor was identified. A nested version of this model was deemed to be the preferred model, which also demonstrated good psychometric properties. CONCLUSION: There is evidence of a ‘general sleep difficulties’ factor in children with ADHD. Four of the six original factors were replicated in this study. However, the revised factor structure suggests that clinicians should be cautious of the utility of subscale scores pending further validation in ADHD samples.